Conflicts and Returns to Stability in Developing Countries : A Comparative Analysis - Fofack, Hippolyte (2012)
Sub-Saharan Africa's dismal development outcomes -- growth collapse and declining real income -- are often used to highlight its sharp development contrast with other regions of the developing world. Drawing on a large cross-section analysis, this paper shows that Africa's underlying dismal records can also be largely accounted for by the skewed distribution of growth in the post-independence era. In particular, structurally low investment rates in a context of high political risk and uncertainty undermined growth prospects in the region. However, counterfactual simulations based on a variation of neoclassical growth models and under the hypothetical equalization of political risk profile alternative result in large economic returns, reflected in the significantly higher level of aggregate output and income in the subset of conflict-affected countries. Income gets even higher when the hypothetical reduction of political risks alternative is accompanied by sustained increases in capital accumulation.